Functional activity and role of cation-efflux family members in Ni hyperaccumulation in Thlaspi goesingense - Persans, Michael W. (National Academy of Sciences, 2001)
The ability of Thlaspi goesingense to hyperaccumulate Ni seems to be governed in part by enhanced accumulation of Ni within leaf vacuoles. We have characterized genes from T. goesingense encoding putative vacuolar metal ion transport proteins, termed metal tolerance proteins (TgMTPs). These proteins contain all of the features of cation-efflux family members, and evidence indicates they are derived from a single genomic sequence (TgMTP1) that gives rise to an unspliced (TgMTP1t1) and a spliced (TgMTP1t2) transcript. Heterologous expression of these transcripts in yeast lacking the TgMTP1 orthologues COT1 and ZRC1 complements the metal sensitivity of these yeast strains, suggesting that TgMTP1s are able to transport metal ions into the yeast vacuole in a manner similar to COT1 and ZRC1. The unspliced and spliced TgMTP1 variants differ within a histidine-rich putative metal-binding domain, and these sequence differences are reflected as alterations in the metal specificities of these metal ion transporters. When expressed in yeast, TgMTP1t1 confers the highest level of tolerance to Cd, Co, and Zn, whereas TgMTP1t2 confers the highest tolerance to Ni. TgMTP1 transcripts are highly expressed in T. goesingense compared with orthologues in the nonaccumulators Arabidopsis thaliana, Thlaspi arvense, and Brassica juncea. We propose that the high-level expression of TgMTP1 in T. goesingense accounts for the enhanced ability of this hyperaccumulator to accumulate metal ions within shoot vacuoles.